Aquatic specific return to play model for concussion - Leclerc, S. (FINA World Sports Medicine Congress, 18, 2016)
Dr. Suzanne Leclerc (CAN) talks about "Aquatic Specific Return to Play Model for Concussion " at the FINA World Sports Medicine Congress 2016.